2017
DOI: 10.12669/pjms.335.12931
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Non-Suicidal Self-Injury among Children with Autism Spectrum Disorder

Abstract: Objectives:To find the prevalence as well as to identify the predictors as protective and risk factors of Non-Suicidal Self-Injury (NSSI) among children with autism spectrum disorder (ASD).Methods:In this analytical cross sectional survey 83 children with ASD age range from 8 to 18 years were selected through convenient sampling technique from five special schools of Lahore city. The Urdu form of a standardized tool was used to assess NSSI.Results:Statistical analysis indicated overall point prevalence of NSSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
(55 reference statements)
1
16
0
1
Order By: Relevance
“…Only two studies reported prevalence of self-injury across different levels of autism. These studies found that severity of autism is associated with a higher prevalence of self-injury, and moreover, that severity of self-injurious behaviour is associated with more severe autism (Akram et al 2017 ; Folch et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported prevalence of self-injury across different levels of autism. These studies found that severity of autism is associated with a higher prevalence of self-injury, and moreover, that severity of self-injurious behaviour is associated with more severe autism (Akram et al 2017 ; Folch et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Associations between self-injury and mental health problems are common and the vast majority of adolescents who engage in NSSI also have some degree of comorbidity, including post-traumatic stress disorder (PTSD) ( 17 , 18 ), with generally higher levels of traumatic exposure ( 19 , 20 ), depressive disorders ( 21 ), obsessive-compulsive disorder ( 18 ), anxiety ( 22 ), symptoms of borderline personality disorder ( 23 , 24 ), specific phobia ( 21 ), autism ( 25 ), intellectual disability ( 26 ), schizophrenia ( 27 ), and eating disorders ( 28 ). A strong association has also been noted between NSSI and externalizing problems where conduct disorder (CD) and attention deficit hyperactivity disorder (ADHD) are most common ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…These include gastrointestinal disorders (Buie et al, 2010;Cawthorpe, 2017;Chandler et al, 2013;Gorrindo et al, 2012;Hand et al, 2020;Mazurek et al, 2013;Neuhaus et al, 2018;Restrepo et al, 2020;Wang et al, 2011;Wasilewska & Klukowski, 2015), inflammatory dyscrasias (Cawthorpe, 2017), as well as a variety of other conditions, such as cardiac disease (Hand et al, 2020), congenital anomalies (Cawthorpe, 2017;Timonen-Soivio et al, 2015), and seizures/epilepsy (Hand et al, 2020;Isaksen et al, 2013;Lewine et al, 1999;Muñoz-Yunta et al, 2008;Parmeggiani et al, 2010;Viscidi et al, 2013). Furthermore, people with ASD have been shown to be at increased risk for unintentional injury (Cavalari & Romanczyk, 2012;Lee et al, 2008;McDermott et al, 2008), self-injurious behavior (SIB) (Akram et al, 2017;Hand et al, 2020;McDermott et al, 2008;Rattaz et al, 2015;Siegel et al, 2015;Slingsby et al, 2017;Summers et al, 2017), physical abuse (Duan et al, 2015;Mandell et al, 2005;Slingsby et al, 2017), violent crime (Christoffersen, 2019), and/or peer bullying (Hoover & Kaufman, 2018;Hwang et al, 2018;Sterzing et al, 2012). People with ASD also suffer greater injuryrelated mortality compared to the g...…”
Section: Introductionmentioning
confidence: 99%